MULTI ACTOR-BASED APPROACH TO PLANNING DECISIONS FOR CULTURAL INDUSTRIES IN NEW ECONOMY - Onur MENGI; Deniz DENIZ; Ahmet Can OZCAN; Cigdem TARHAN (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2015)
Along with the new economy, the competitive advantage of cities is now derived from management of their cultural productions. However, pottery making as cultural industry including ceramic and other earthenware products, currently suffers from many difficulties as inefficient role of government, environmental problems, and the lack of promotion and marketing strategies and falls behind the recent urban development trends. Menemen-Izmir/Turkey has been selected as case area, where the pottery making inherited for five generations. The aim of this study is to suggest a model to tackle with the current difficulties of and also to develop cultural production. The data have been collected via questionnaire and interviews with the pottery masters and Pottery Makers Association. The research proposes the multi actor-based approach through statistically analyses and maps to manage cultural industries and integrate various actors related to the cultural production into the decision making process of urban planning.